1978
DOI: 10.1002/jsfa.2740290102
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fertiliser N plus K on N, S and other mineral elements in perennial ryegrass at a range of sites

Abstract: Tn an agronomic experiment, perennial ryegrass was grown with four rates of fertiliser N + K at 21 sites in England and Wales. Herbage from two successive harvests at 14 of the sites has been examined for contents of N and S and of other mineral elements in relation to the nutrition of both the crop and ruminant animals. The highest rate of fertiliser application (125 kg N + 77.5 kg K/ha harvest) resulted in contents of total N greater than 4 % at five sites at the second harvest, but nitrate-N reached levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
6
13
0
Order By: Relevance
“…Urea-based fertilizers can have similar efficiencies to ammonium nitrate when applications are conducted in spring but can be lower in summer (Watson et al 1990). In Y1, NUE recorded in urea-and OMF-treated grass were within the range reported in the literature (e.g., Whitehead, Jones, and Barnes 1978;Morrison, Jackson, and Sparrow 1980;, but exceeded those obtained in Y2 which were similar to values obtained by Williams, Rowarth, and Tregurtha (2000).…”
Section: Fertilizer Application Effects On Cropsupporting
confidence: 86%
“…Urea-based fertilizers can have similar efficiencies to ammonium nitrate when applications are conducted in spring but can be lower in summer (Watson et al 1990). In Y1, NUE recorded in urea-and OMF-treated grass were within the range reported in the literature (e.g., Whitehead, Jones, and Barnes 1978;Morrison, Jackson, and Sparrow 1980;, but exceeded those obtained in Y2 which were similar to values obtained by Williams, Rowarth, and Tregurtha (2000).…”
Section: Fertilizer Application Effects On Cropsupporting
confidence: 86%
“…Management optimization of temporary grassland systems, which are only kept for a few years (Allen et al 2011) must take species traits and soil fertility into consideration (Whitehead et al, 1978;Hopkins et al, 1994).…”
Section: G Kgmentioning
confidence: 99%
“…However, many pasture plants supply other elements that influence the performance of those ingesting the herbage. Belesky et al (2001) investigated mineral composition in pure stand chicory and Whitehead et al (1978) in pure stand ryegrass but studies in mixtures have also been reported (Whitehead et al, 1983, Lawes & Gilbert, 1990, Hopkins et al, 1994. Hopkins et al (1994) described the variation in selected macro-and micro-mineral concentrations in Lolium perenne/Trifolium repens-dominated swards over seasons and over years (Hopkins et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that increasing rates of N fertilizer to perennial ryegrass alters the ratios of N: S and of K :( Ca and Mg) (Whitehead et al 1978). Hopkins et al (1994) concluded that applied N reduced concentrations of Ca, Mn and S and increased those of Mg, Na and Zn, with no consistent effects on concentrations of K and Cu in herbage of perennial ryegrass.…”
Section: Introductionmentioning
confidence: 99%